(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study assessed the effectiveness of demonstration method in entrepreneurship education in tertiary institutions in South-South Nigeria. The objective of the study was to determine the effectiveness of the demonstration method in teaching entrepreneurship education in tertiary institutions in South-South Nigeria. A descriptive survey method was adopted. Questionnaire was used to sample opinions of 684 lecturers selected by stratified random sampling from a total population of 13,607 lecturers. The results of the study were presented using tables and frequencies. Analysis of variance was used in analyzing the hypothesis. The findings indicate that demonstration method was effective in teaching entrepreneurship education in tertiary institutions in South-South Nigeria. Based on the findings, it was concluded that using demonstration method in teaching entrepreneurship education is effective. It was recommended that entrepreneurship education lecturers should make concerted efforts to use demonstration teaching method that is considered effective in teaching their students